2019
DOI: 10.15407/ujpe64.10.927
|View full text |Cite
|
Sign up to set email alerts
|

Magnon Bose–Einstein Condensate and Supercurrents Over a Wide Temperature Range

Abstract: Einstein Condensates (BECs) and supercurrents are coherent quantum phenomena, which appear on a macroscopic scale in parametrically populated solid state spin systems. One of the most fascinating and attractive features of these processes is the possibility of magnon condensation and supercurrent excitation even at room temperature. At the same time, valuable information about a magnon BEC state, such as its lifetime, its formation threshold, and coherency, is provided by experiments at various temperatures. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For instance, there are only a few experiments done at room temperature to demonstrate the possibility of magnon state squeezing [452], magnon BEC supercurrents, and Bogoliubov waves [429], [430], [453]. The only attempt to study magnon BEC at cryogenic temperatures was reported in [454] but a thorough investigation in the quantum limit is still needed.…”
Section: B Yig-based Quantum Magnonicsmentioning
confidence: 99%
“…For instance, there are only a few experiments done at room temperature to demonstrate the possibility of magnon state squeezing [452], magnon BEC supercurrents, and Bogoliubov waves [429], [430], [453]. The only attempt to study magnon BEC at cryogenic temperatures was reported in [454] but a thorough investigation in the quantum limit is still needed.…”
Section: B Yig-based Quantum Magnonicsmentioning
confidence: 99%
“…Alternatively, magnon BEC coherence can be tested indirectly by observation of phenomena such as quantized vorticity [29], supercurrents [30], Bogoliubov waves [31], or Josephson oscillations [32], which are canonical features of both atomic and quasiparticle quantum condensates. Our studies of some of these phenomena [30][31][32][33][34] have shown that they occur only in a freely evolving magnon gas after switching off the microwave pumping. This takes place probably because the intense pumping process prevents condensation by heating the magnon gas [13] and mixing the magnon frequencies near the bottom of their spectra [28].…”
mentioning
confidence: 90%
“…Very recently, the fields of quantum magnonics and magnonics at cryogenic temperatures were established. Among the highlights, one should mention the first realization of coherent coupling between a ferromagnetic magnon and a superconducting qubit [32], the first observation of the interaction between magnons and Abrikosov fluxes in superconductorferromagnet hybrid structures [33], the investigation of the interplay of the magnetization dynam-ics with a microwave waveguide at cryogenic temperatures [34] and many more interesting phenomena [35][36][37]. Thus, the understanding of the influence of the temperature on spin pinning conditions and on the spin-wave dispersion in nanostructures is of high demand.…”
Section: Introductionmentioning
confidence: 99%